2014
DOI: 10.2147/jpr.s46929
|View full text |Cite
|
Sign up to set email alerts
|

Programmable intrathecal pumps for the management of chronic pain: recommendations for improved efficiency

Abstract: The management of chronic pain can be very challenging. Often, physicians employ intrathecal (IT) drug delivery systems as a last resort to relieve intractable pain. The system consists of an implantable pump that stores and delivers medication through a catheter to the IT space. Programmability is achieved by positioning an external devise over the implanted pump to change the mode of drug delivery. The innovations in programmable IT drug delivery systems are expanding more rapidly than ever before. Unfortuna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Oligonucleotide delivery using osmotic pumps is a recognized technique with potential therapeutic applications in mammals including humans. 45 , 46 , 47 , 48 We therefore used this strategy to deliver miR-16 mimics into the mouse brain. We chose wild-type mice—instead of AD mice—for these in vivo preclinical studies since harboring all physiological regulatory elements ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Oligonucleotide delivery using osmotic pumps is a recognized technique with potential therapeutic applications in mammals including humans. 45 , 46 , 47 , 48 We therefore used this strategy to deliver miR-16 mimics into the mouse brain. We chose wild-type mice—instead of AD mice—for these in vivo preclinical studies since harboring all physiological regulatory elements ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Breakthrough pain in patients managed with an intrathecal delivery system historically required additional oral pain medication, which necessitated a physician office visit. The versatility of TDD hardware and software has evolved from devices capable of simple continuous nonprogrammable flow, to TDD systems with time and daily‐programmable variable modes . Optimizing programming algorithms received attention after physicians treating spasticity demonstrated that baclofen tolerance can be reversed when the agent is administered by daily timed bolus rather than continuous infusion .…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] Successful clinical implementation of the implantable pump requires significant training of the physicians. [ 32 ] Additionally, the implantable pumps are not cost-effective in patients with short life expectancy. [ 10 ] An external drug infusion is used as an alternative approach in cancer patients with a short life expectancy.…”
Section: Discussionmentioning
confidence: 99%